Penerapan Pendekatan Pembelajaran Individual Berbasis Talaqqi dalam Pembelajaran Membaca Alquran di SMA Muhammadiyah 2 Medan - Antika, Siti Windya (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze the implementation of an individualized learning approach based on the talaqqi method in improving students’ ability to read the Qur’an at SMA Muhammadiyah 2 Medan, covering aspects of planning, implementation, evaluation, and the challenges encountered. This research employs a qualitative approach with a phenomenological method, using observation, interviews, and documentation as data collection techniques. The findings indicate that the implementation of the individualized talaqqi-based approach is carried out systematically through well-structured planning, personalized and interactive learning processes between teachers and students, and continuous evaluation to monitor students’ progress. This approach has proven effective in enhancing reading accuracy, understanding of tajwid rules, fluency, and students’ confidence in reading the Qur’an. However, several challenges remain, including low student motivation and readiness, limited parental support, and less conducive learning environments and media. Therefore, strong synergy among schools, teachers, and families, as well as improvements in pedagogical competence and learning facilities, are essential to optimize the sustainable implementation of this approach.